Analysis of energy consumption of two kinds of edge caching strategies in heterogeneous networks - Yi SUN; Hong WANG; Rongfang SONG (Dianxin kexue)
The energy consumption of a two-tier heterogeneous network under two different caching strategies was analyzed.Firstly,the energy consumption of each network components was modelled,and the relationship between the energy consumption of heterogeneous networks and the distribution density of small cell,user load per cell and caching capacity was investigated.The simulation results show that edge caching can effectively reduce the energy consumption of heterogeneous networks and the performance of the two caching strategies are different under different density of small base station and user load.Specifically,the energy consumption of both the network and per user under the two caching strategies are reduced with the increase of the density of small base station and the user load per cell,respectively.Furthermore,the influence of small base station’s caching capacity can not be neglected in total energy consumption.